A review of the Nearctic species of Erythmelus (Hymenoptera: Mymaridae), with a key and new additions to the New World fauna - Triapitsyn, Serguei V.; Berezovskiy, Vladimir V.; Hoddle, Mark S.; Morse, Joseph G. (Zootaxa, 2007)
The 12 Nearctic species of the fairyfly genus Erythmelus Enock (Hymenoptera: Mymaridae) are revised, and the described species in the Neotropical region are reviewed. A key to females of the 30 named, valid species of Erythmelus in the New World is provided. Erythmelus vladimir S. Triapitsyn & Fidalgo is transferred from subgenus E. (Parallelaptera) Enock to the nominate subgenus as E. (E.) vladimir comb. n. Erythmelus dentatus Ogloblin is synonymized under E. (E.) brachialis Ogloblin, E. empoascae Subba Rao is synonymized under E. (E.) flavovarius (Walker), E. flandersi Doutt is synonymized under E. (E.) picinus (Girault), E. gracilipes (Girault) and E. io (Girault) are synonymized under E. (E.) gracilis (Howard), and E. longicornis Dozier is synonymized under E. (E.) noeli (Dozier). A lectotype is designated for E. (E.) picinus. The following new species are described: E. (E.) burtik S. Triapitsyn (Canada), E. (E.) coviellai S. Triapitsyn (Argentina), E. (E.) fidalgoi S. Triapitsyn (Argentina), E. (E.) gak S. Triapitsyn (Chile), E. (E.) klopomor S. Triapitsyn (USA), E. (E.) logarzoi S. Triapitsyn (Argentina), E. (E.) mikrob S. Triapitsyn (Canada), E. (E.) mudrila S. Triapitsyn (Mexico and USA), E. (E.) podaypodnos S. Triapitsyn (Bolivia), and E. (E.) toreador S. Triapitsyn (Argentina). A synopsis of the included species is given, with emphasis on their distributional records and known host associations in the families Miridae and Tingidae (Hemiptera).